Implementasi Kebijakan Pengembangan dan Pemberdayaan UMKM di Kelurahan Jeruk Kecamatan Lakarsantri Kota Surabaya - Ryan Gymnastiar Alwin; Dida Rahmadanik (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The Jeruk Village in Surabaya is one of the areas that have many Micro, Small, and Medium Enterprises (UMKM) with various types of businesses such as culinary, convenience stores, laundry services, and garment shops. In an effort to maintain legal certainty and enhance the capacity of business actors in facing trade competition in the area, the Surabaya City Government officially enacted Regional Regulation Number 1 of 2021 on the Development and Empowerment of Micro Enterprises. Research results show that the local and sub-district governments provide comprehensive services to the community, especially UMKM that have business permits. The socialization conducted by the Lakarsantri Sub-District in Surabaya includes explanations about the Business Identification Number (NIB) to UMKM actors. Moreover, they also provide support in the business permit application process, including issuing business codes as a form of business activity legality. The implementation of UMKM development and empowerment policies in the Jeruk Village, Lakarsantri Sub-District, Surabaya, reflects several indicators in the Policy Implementation Theory by Merilee S. Grindle. The Lakarsantri Sub-District, especially Jeruk Village, has diligently and effectively implemented this policy, as reflected in various activities, ranging from raising awareness to assisting in the business permit application process. The benefits of this policy are directly felt by both the government and the UMKM owners.